The Influence of the Use of Facebook as a Marketing Media on the Income of Muslim Traders in Sapugara Bree Village, Brang Rea District, West Sumbawa Regency - Maulana, Bayu; Agustina, Ahadiah; Fitri Hidayanti, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to evaluate the effect of using Facebook as a marketing medium on the income of Muslim traders in Sapugara Bree Village, Brang Rea District, West Sumbawa Regency. This research used quantitative methods involving 22 Muslim traders in Sapugara Bree Village. The collected data was analyzed using SPSS Version 23 statistical techniques on the Windows 10 operating program. Before using Facebook or digital marketing, traders usually offered their goods or services door to door, through local radio advertisements, through word of mouth using marketing services, brochures, and pamphlets or leaflets. The research results showed that the use of Facebook as a marketing medium had a significant positive impact on the income of Muslim traders in Sapugara Bree Village. The statistical test results show 19.7%. This research provides an important contribution to strengthening our understanding of the role of Facebook as a marketing medium in increasing the income of Muslim traders. The implication is that Muslim traders in Sapugara Bree Village need to optimize the use of Facebook as an effective marketing strategy to increase their sales and compete in the digital business era.